THE SYSTEM OF SUPPORTING CHARACTERS IN THE “OGHUZNAME” EPIC - Zahro Khaydarova (International Journal of Literature and Language Studies, 2026)
This article examines the secondary characters that surround the central hero of the “Oghuzname” epic, Oghuz Khan: the blue wolf, Oy Qaghan, Ulugh Turk, and the hero’s two wives and six sons. Rather than treating these figures as isolated decorative elements, the study approaches them as an interconnected symbolic system in which each character reinforces a distinct source of the hero’s authority - divine, genealogical, cosmic-territorial, and intellectual-political. The analysis shows that, taken together, these images form a three-tiered cosmological model (sky - earth - horizontal political space) that artistically substantiates Oghuz Khan’s status as ruler of the entire world.